The effects of international remittances on poverty, inequality, and development in rural Egypt - Adams, Richard H., Jr. (International Food Policy Research Institute, 1991)
Despite their importance, there has been little analysis and even less agreement about the effects of international remittances on the economies of labor-exporting countries. Do households with migrant workers squander the money earned abroad on newly desired consumer goods? Are remittances largely earned by the sons of already well-to-do households? Do remittances increase the degree of income inequality between richer and poorer rural households? In this report, the author examines these issues from the standpoint of a small area of rural Egypt. Adams uses income data from households with and without migrants to determine the effects of remittances on poverty, income distribution, and rural development. The study is based on a survey of 1,000 households conducted in 1 986/87 in three villages in Minya Governorate, a province about 250 kilometers south of Cairo. In a second round of the survey, 150 selected households were interviewed about their spending behavior. Although the research is based on rural Egypt, its findings are relevant for policymakers in other labor-exporting countries.